2009
DOI: 10.1055/s-0029-1214979
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological factors associated with clinical outcomes of endoscopic submucosal dissection for colorectal epithelial neoplasms

Abstract: The present study provides useful information for predicting risks for incomplete resection and complication in colorectal ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
164
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(191 citation statements)
references
References 13 publications
20
164
1
4
Order By: Relevance
“…Delayed perforation as a serious complication after ESD was demonstrated in several studies, with rates ranging from 0.3-0.7%. 25,26,33 No case of delayed perforation was verified in our study.…”
Section: Discussionmentioning
confidence: 48%
“…Delayed perforation as a serious complication after ESD was demonstrated in several studies, with rates ranging from 0.3-0.7%. 25,26,33 No case of delayed perforation was verified in our study.…”
Section: Discussionmentioning
confidence: 48%
“…Factors such as large tumor size, laterally spreading tumors, tumor location (right-sided colon), submucosal injection without hyaluronic acid, severe fibrosis, and deep-submucosally invasive cancer were associated with a higher rate of perforation in other studies [8,10,20,21] . On the other hand, poor endoscopic operability was also reported to be related with perforation [22] .…”
mentioning
confidence: 67%
“…tumors and fibrosis were significantly associated with incomplete en bloc resection [20] . Another study reported that poor endoscopic operability and deep submucosal invasion were significantly related to incomplete en bloc resection [21] . Similar to these reports, our present study showed that severe fibrosis and difficult manipulation were related to incomplete resection.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan and some other Western and Asian countries, endoscopic submucosal dissection (ESD) is reported to be an efficient treatment with a high rate of en bloc resection for large colorectal tumors and it is considered less invasive than laparoscopic colectomy (LAC) [75][76][77][78][79][80][81][82][83]. However, ESD can be a time-consuming procedure and carries a higher risk of perforation than EMR [81,82].…”
Section: Endoscopic Submucosal Dissectionmentioning
confidence: 99%
“…Thirdly, lesions other than these cases can be an indication for ESD, including mucosal lesions with fibrosis caused by prolapse due to biopsy or peristalsis of the lesions, local residual early cancer after endoscopic resection, and sporadic localized tumors in chronic inflammation such as ulcerative colitis. The rate of en bloc resection for large colorectal tumors by ESD has been reported to be 80-98.9% [75][76][77][78][79][80][81][82][83] (Table 6). However, the procedure has not been standardized because of its associated technical difficulties.…”
Section: Endoscopic Submucosal Dissectionmentioning
confidence: 99%